Meriones Illiger 1811 - James H. Honacki; Kenneth E. Kinman; James W. Koeppl (Alien Press, Inc. & The Association of Systematics Collections, 1982)
Meriones Illiger, 1811. Prodr. Syst. Mamm. et Avium., p. 82. REVIEWED BY: D. M. Lay (DML); C. B. Robbins (CBR); O. L. Rossolimo (OLR); S. Wang (SW). COMMENT: Formerly included Sekeetamys; see Petter, 1956, Mammalia, 20:419-426, Petter, 1975, Part 6.3:4, and Corbet, 1978:124. Reviewed by Chaworth-Musters and Ellerman, 1947, Proc. Zool. Soc. Lond., 1947- 1948:478-504; Arabian species reviewed by Harrison, 1972, The Mammals of Arabia, 3:559-593; African species are in need of revision (see Corbet, 1978:125). Sokolov and Orlov, 1980:156, included Brachiones przewalskii in Meriones, without comment; but see Corbet, 1978:128. Subfamily Gerbillinae; see comment under Cricetidae. ISIS NUMBER: 5301410008092000000. Published as part of James H. Honacki, Kenneth E. Kinman & James W. Koeppl, 1982, Order Rodentia (Part 3), pp. 392-476 in Mammal Species of the World (1 st Edition), Lawrence, Kansas, USA :Alien Press, Inc. & The Association of Systematics Collections on pages 423-424, DOI: 10.5281/zenodo.7353031